The role of political non-violence in changing the regimes A theoretical study, with a focus on the Egyptian political non-violence movement, January 25, 2011 - Mawlud, Imad Ahmed (Journal of Legal and Political Studies, 2023)
What distinguishes political non-violence is its peacefulness and perhaps its spontaneity. The pacifism of non-violence lies in the rejection of violence or resorting to the use of force to change the regime of government or to exert pressure on the government to achieve a specific goal that may be political, economic or social. Pre-planning against the government, but there are political non-violence movements that may adopt programs and plans studied in advance. So it depends on the nature of the political nonviolence movements; (There are political nonviolent movements that mainly believe in the peaceful option and reject violence, and others are also peaceful movements, but may resort to the use of violence, even in its primitive form), or it depends on the nature of the regime they are facing; There are authoritarian and totalitarian regimes that confront their opponents by using excessive force against them, and other democratic regimes that allow the political nonviolence movements to express their demands through various forms; (Peaceful demonstration, civil disobedience, strike, protest, boycott... etc.). There are semi-authoritarian or semi-democratic regimes that may succumb to the demands of political non-violence movements. As is the case with the Egyptian political regime, which gave in to the demands of the January/ 25/ 2011 movement, and as a result, former Egyptian President Hosni Mubarak stepped down from power on February /11/ 2011 during 18 days of continuous demonstrations, protests and civil disobedience.
Keywords: Political NonViolence; Egypt; violence; demonstrations; Protests; Civil Disobedience